Kant’s Moral Principles as Guidelines in Addressing the Issue of Cyberbullying - Kleden, Fransiskus Bala; Ule, Silvester; Rizan Pryatno, Emanuel (Litbang STFT Widya Sasana Malang, 2025)
Cyberbullying has become a very crucial problem along with the increasing use of digital media in Indonesia. Its problem generally targets children and teenagers as the most dominant victims. This research attempts to explore the polemic of cyberbullying and offers Immanuel Kant’s moral principles as the main guideline in responding to it. In completing this article, the author used the qualitative-descriptive method with literature studies and interviews. The author first describes the case study of cyberbullying and analyzes that problem. To respond to this phenomenon, the author presents Immanuel Kant’s moral principles and draws their relevance for responding to cyberbullying cases. The research results state that, according to Kant, efforts to combat cyberbullying crimes are a categorical imperative that cannot be rejected by anyone. Cyberbullying can be stopped by strengthening moral principles in humans,which are the principles of universality, humanity, and moral autonomy. These three principles can be implemented into concrete virtues such as the internalization of individual responsibility, the formation of character education appropriate to the contextual digital era, and the implementation of practical moral values in life. These virtues invite people to respect the dignity and autonomy of others, which directly challenges the practice of cyberbullying. By having and doing this, humans are trained to sharpen their moral sensitivity in treating others while being wise and responsible in using existing technological media.